Political Connections, Blockholder Ownership, and Tax Avoidance: Evidence from Indonesia - Lutfi Yuli Handoko; Maria Mediatrix Ratna Sari; I Gusti Ngurah Agung Suaryana; I Gusti Made Asri Dwija Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
We study the effect of political connections on tax avoidance, as well as the role of blockholder ownership in moderating the effect of political connections on tax avoidance. Using panel data of 102 companies listed on the Indonesia Stock Exchange during 2016–2019, we find evidence of the positive and significant effect of political connections on tax avoidance. Political connections’ existence within the company could encourage tax avoidance. We also discover that blockholder ownership plays a role in weakening the effect of political connections on tax avoidance in Indonesia, a country with numerous companies having concentrated ownership. The higher the percentage of shares owned by the blockholder, the lower the level of tax avoidance, thus mitigating agency problem II related to entrenchment and expropriation of minority shareholders.